Legal-system arbitrage and parent – subsidiary capital structures - Banerjee, S; Noe, T (INFORMS, 2016)
This paper develops a new theory of the capital structure of parent–subsidiary organizations based on legal-system arbitrage: The capital structure of parent–subsidiary organizations is chosen to minimize the agency costs generated by selective renegotiation of claims written on the component legal entities. We show that optimal mixes of parent– subsidiary level financing minimize the default premia associated with the organization’s overall financing package by equating the marginal enforceability of debt contracts written at the parent and subsidiary level. The enforceability of creditor claims depends not only on the legal regime but also on the size of the debt claims and the liquidation value of the firm’s assets. Small claims written under a weak creditor rights regime may be more enforceable than large claims written under a regime with strong creditor protection. Thus, all optimal mixes involve some borrowing at the subsidiary level even if the subsidiary legal regime features weaker creditor protection than the parent regime. However, the mix between parent and subsidiary financing tilts toward the regime that features stronger creditor protection.